IMPLEMENTASI JAMINAN KESEHATAN NASIONAL DI TINJAU DARI ASPEK PELAYANAN KESEHATAN DAN ASPEK KINERJA - Ririn Wahyuni Gobel (Jurnal Administrasi, Manajemen dan Ilmu Sosial, 2024)
This research aims to determine the process of implementing National Health Insurance in Buol Regency, including: regulatory aspects, number of participants, aspects of benefits and contributions, and aspects of health services. The research method used descriptive qualitative, research locations in Buol Regency included the Health Service, Social Service, Head of BPJS Managing JKN, Village Head and Village officials in Bokat District, PBI Participants in Bokat District, Head of Bokat Community Health Center. Data collection techniques include observation, interviews and documentation which are then analyzed using qualitative data based on the Miles and Huberman concept. The research results show that the implementation of the JKN program in Buol Regency has been implemented well but is not yet optimal, this can be seen in the aspects: a) regulations. Implementation of the JKN program in Buol Province has succeeded in achieving a 75% increase in health services. However, optimal and sustainable results are not achieved due to frequent changes and lack of outreach efforts, b) The number of participants continues to increase but has not yet met the standardized achievements due to tiered management, overlapping data, and lack of outreach so that there are still many that have not been covered in JKN.